Imperialissima-mästaren som kategoriseringsproblem - Bonsdorff, Jan von (Hikuin, 1999)
The Imperialissima-master as a Problem of Categorization By Jan von Bonsdorff The author takes the so-called “Imperialissimameister” as a pretext to delineate different methodical approaches to the taxonomy of art-historical research on late medieval wooden sculpture in Northern Europe. One main working method during the earlier part of the 20th century was the attributional strategy. The positioning of the work of art in connection with a name was deemed as a final art-historical result. Furthermore, the author discusses a posible source of the inscription giving the name of the anonymous master: Imperialissima virgo Maria. The text is similar to typical mariological attributes from contemporary prayers. The author turns to works that formerly have been ascribed to the “Imperialissimameister”. He proposes a contextual approach, founded on the concept of the workshop, and presents three reasons why he thinks that most of the works are fabricated in small, local workshops on Jutland and in Slesvig-Holsten: the tradition is unbroken through predecessors and followers; the Lübeck production of wooden sculpture stagnates shortly after 1500; and there is no lack of craftsmen in local centres. Of course, the workshop is only a part of the over-all context. The author proceeds to discuss the panofskyian myth of the readable intellectual all-explaining context. He points to the fact that knowledge of iconographien content is unevenly distributed within the social net, and that the possibility of “empty signs” remains, i. e., that followers of the original work of art were designed without the knowledge of the intellectual program in the first work. Furthermore, the author states that the social, religious and cultural net makes place for the medieval work of art – but the craftsman is responsible for the visual solutions, i. e., also for “style”.